Direct Torque Control of a Doubly Fed Induction Generator - Asma Ben Amar (International Journal of Energetica)
In this paper a direct torque control system is proposed and is applied to doubly fed induction generator (DFIG) based wind power generation systems. In this control system the rotor flux and the electromagnetic torque are estimated based on the rotor voltage and currents measurements. The validity and effectiveness of this control is demonstrated by some simulation results.